Circular economy: An international needs analysis for vocational learning in small and medium-sized enterprises - Anett Wolgast; Caroline Pape; Metje Rocklage (International Journal for Research in Vocational Education and Training (IJRVET), 2026)
Context: Extensive theory-based research on academic and vocational education has long explored the connections between emotions, motivation, and learning as drivers of behavioral change in occupational contexts. Emotions and motivations play a crucial role in shaping how individuals and organizations adopt new practices, yet their role in fostering larger-scale shifts, such as the transition to a circular economy, has received limited attention. Meanwhile, the global shift toward a circular economy has gained increasing priority, with governments, industries, and international organizations promoting various initiatives aimed at encouraging companies, particularly small and medium-sized enterprises (SMEs), to adopt sustainable, resource-efficient, and circular practices. These initiatives predominantly emphasize the cognitive and practical dimensions of circular economy strategies, focusing on actionable knowledge and technical skills. However, the emotional drivers-such as enthusiasm, apprehension, or resistance-of such transformative changes are often overlooked. Sentiments, which significantly influence individual and collective behaviors, could be critical to understanding how ready SMEs are to embrace circular economy principles. Despite their importance, the role of sentiments in shaping organizational and behavioral responses to circular economy transitions remains underexplored and warrants further investigation. Approach: Grounded in the multiple R framework and Plutchik's multifactor-analytic theory of emotion, this study sought to address this gap by analyzing the sentiments expressed by SME members. We conducted a sentiment analysis on statements from employers and employees across 100 SMEs in Germany, Italy, and Poland. Findings: The results indicate that the overall sentiment among SME members was predominantly positive, suggesting that these companies are largely optimistic and supportive of transitioning to circular economy practices. This positive outlook implies that emotional attitudes are not the primary barriers to adopting circular economy principles. Instead, systemic challenges-such as regulatory, infrastructural, and financial barriers-appear to be the main obstacles impeding SMEs' progress toward circular practices. Conclusions: Our findings underscore the need for more comprehensive systemic vocational education on circular economy practices to better equip SMEs for this transition. Understanding this need provides valuable insights into the real-world challenges faced by SMEs and emphasizes the importance of addressing structural barriers to facilitate this critical transformation. By considering both cognitive and emotional dimensions, this study sheds light on key factors influencing the adoption of circular economy practices in SMEs, ultimately supporting policymakers and business leaders in devising more effective strategies for sustainable development and economic resilience.
Keywords: 330; Green Economy; Needs Assessment; Small and Medium Enterprises; Employers; Continuing Vocational Education and Training; VET